Exercise and wellness for older adults practical programming strategies - Van Norman, Kay A. 1957- (Human Kinetics, 2010)
Exercise and Wellness for Older Adults, Second Edition, is an introduction to aging and wellness and an essential guide to creating exercise and wellness programs for older adults, regardless of age or physical challenge. Readers will find the latest information on strength and power training and learn how to apply it to improve the functional abilities of older adults. The text provides a framework to help readers make the critical shift from expectations of decline to an age-neutral focus on maximizing functional ability. The text, formerly titled Exercise Programming for Older Adults, has been thoroughly updated to reflect the broad-based focus encompassing all aspects of wellness rather than just fitness. The author introduces the whole-person wellness concept, which fully engages individuals and helps them succeed in their pursuit of lifelong health and well-being. Specific strategies and exercises are presented to help professionals integrate the six dimensions of wellness (physical, social, emotional, intellectual, spiritual, and vocational) into their programs. This edition includes a new chapter on identifying and overcoming the unseen or overlooked psychosocial barriers to participation in wellness programs and engaging adults in healthy habits. It also offers new information on program development, including techniques for creating and promoting programs in both senior living and community-based environments. Like the first edition, Exercise and Wellness for Older Adults continues to provide a collection of easy-to-follow exercises for both water- and land-based programming. The book also offers guidelines on addressing programming for adults with functional limitations and special conditions. Both students and professionals can learn and improve programming efforts using the following features: 120 land-based programming options including chair, chair-assisted, low-impact aerobic, and resistance-training exercises; 72 water-based programming options including range of motion, flotation and aerobic exercises, and exercises for clients with arthritis, all fully illustrated with underwater photos; Case studies and testimonials that illustrate the potential results from participation in wellness and exercise programs; A progression of exercises for both land- and water-based programs that allow greater flexibility to meet individual needs; Wellness wrap-ups at the end of each chapter that emphasize the psychosocial aspects that can enhance and promote exercises and overall wellness; Project MOVE, an approach that uses psychosocial research to motivate older adults to engage in wellness offerings. Exercise and Wellness for Older Adults gives readers the knowledge and tools to change their mind-set and approach to programming, helping their clients improve their overall fitness, health, and vitality.